Gender Quotas, Board Diversity and Spillover Effects. Evidence from Italian Banks - Silvia Del Prete; Giulio Papini; Marco Tonello (Global Labor Organization (GLO), 2024)
We study the impact of a law, which required the increase of the proportion of women on boards of listed companies to at least one third. We look at its impact on listed banks, but also test whether it led to spillovers into non-listed banks belonging to listed groups or along other board diversity dimensions. Using administrative data, we compare diversity measures of boards of listed and non-listed banks in listed groups with those in non-listed groups, before and after the introduction of the law, in a difference-in-differences specifi- cation. We find that the imposition of the gender quota only changed the composition of the boards of listed banks, with no effect on their economic performance, nor spillovers on other non-listed banks in listed groups. The law enhanced diversity of boards of listed banks, also along individual characteristics other than gender.
Keywords: G21; G38; J48; J78; 330; bank boards; diversity; gender; corporate governance